REFLECTIVE FEATURES OF PSYCHOLOGICAL ADAPTATION IN STUDENT PERIOD - Dedakuziyeva Barchinoy Mahamadjonovna (Journals Park Publishing, 2022)
The article describes the students and their psychological characteristics, one of the most pressing issues of today, the research work on this topic, the views of scientists.
Keywords: article; higher education; education